Pengaruh Green Marketing dan Nilai Pelanggan terhadap Keputusan Pembelian dan Loyalitas Pelanggan untuk Inovasi Produk Makanan Sehat - Laeli Ana Slavia Pratiwi; Budi Setiawan; Fitria Dina Riana (Jurnal Penelitian Pendidikan IPA, 2025)
The growing demand for healthy and environmentally friendly food products has encouraged businesses to adopt green marketing strategies and provide greater customer value. This study aims to analyze the influence of green marketing and green customer value on purchase decisions and customer loyalty in healthy food product innovation. A quantitative method was employed using purposive sampling of 100 respondents who had purchased Green Rebel products in the Jabodetabek area. Data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships among variables, including purchase attitude and purchase intention as mediators. The findings reveal that green marketing and green customer value significantly affect purchase decisions, both directly and indirectly through purchase attitude and purchase intention. However, their influence on customer loyalty was limited. These results indicate that although green marketing and customer value enhance consumer purchasing behavior, maintaining loyalty requires additional strategies such as product certification, stronger promotional activities, and highlighting sustainability and health benefits. This study contributes to the understanding of consumer behavior in healthy food innovation and provides managerial insights for companies seeking to strengthen competitiveness in the sustainable food industry.